IDENTIFIKASI AMPHETAMINE, METHAMPETAMINE DALAM URINE SISWA SMA “X” METODE STRIP STICK - Dyna Grace Romatua Aruan; Maniur Arianto Siahaan (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Amphetamines called alpha-methyl-phenethylamine, beta-phenyl-isopropylamine, or benzedrine are a class of simulants used to treat hyperactivity disorder due to inattention in adults and children. Methamphetamine is a drug that belongs to the amphetamine class. It works the same way as amphetamine can increase alertness, concentration, and when taken at high doses can cause euphoria. In general, marijuana is used through cigarettes, including the hallucinogenic drug group and class 1 drugs. The harmful impact of drugs on adolescents and especially for students is that drug use can cause negative effects that will cause mental and behavioral disturbances in a person, resulting in disruption of the neuro-transmitter system in the brain. nerves in the brain. Amphetamine and methampetamine levels were lowest in stems, roots and seeds, while the highest levels were found in flowers, sap and leaves. The type of research carried out is a qualitative analysis with the method of examining samples using ICT (Imunochromatography Test) with amphetamine and methamphetamine strips/sticks. The population in this study were 15 students of class XI SMA "X". The research conducted, took all the urine of class XI students. The urine collection process was carried out at the "X" School and then examined directly at the Science Laboratory in March 2022. The results of the overall urine sample examination were negative for amphetamine and methampetamine.